The Impact of Comprehensive Sex Education on Adolescents' Understanding and Prevention of Sexual Violence - Maranatha, Ailsie Adriella (IHSA Institute, 2024)
This study investigates the impact of comprehensive sex education on adolescents' understanding, attitudes, and behaviors related to sexual violence. Using a mixed-methods approach, the research combines quantitative surveys and qualitative interviews to assess changes in knowledge, attitudes, and behaviors among adolescents who participated in a structured sex education program. The findings reveal that comprehensive sex education significantly improves students' knowledge about sexual violence and consent, fosters more positive and respectful attitudes, and leads to reductions in risky and coercive sexual behaviors. The study also highlights the importance of cultural sensitivity and inclusivity in program design, noting that tailoring education to diverse cultural contexts enhances its effectiveness. However, challenges such as inconsistencies in curriculum delivery, cultural and social barriers, resource constraints, and the need for continuous program evaluation are identified as limitations that impact the success of sex education initiatives. The research underscores the need for ongoing investment and refinement of sex education programs to address these challenges and ensure equitable access and effectiveness. The study contributes to the broader understanding of how sex education can play a crucial role in preventing sexual violence and promoting healthy relationships among adolescents.